Assessing the impact of land use and liming on stream quality, diatom assemblages and juvenile salmon in Wales, United Kingdom. (February 2021) - Jüttner, I.; Kelly, M.G.; Evans, S.; Probert, H.; Orange, A.; Ector, L.; Marsh-Smith, S.
Graphical abstract: Highlights: The UK acidification index (DAM) highlighted acidification in upland streams. Liming led to recovery of water chemistry and a shift from acid tolerant to acid sensitive diatom species. Juvenile salmon increased and returned to upstream areas in the River Wye and Irfon. Abstract: Many freshwaters in base-poor upland areas of Britain continue to be affected by acidification as a result of deposition of air pollutants, and agricultural and forestry practices. The effects of land use and annual liming on stream chemistry, diatoms and salmon populations were investigated over eight years in the upper catchment of the River Wye, Wales, United Kingdom. Variations in water chemistry, diatom species composition and diversity, and in the index Diatom Acidification Metric (DAM) were compared between different types of land cover and flow conditions, and before and after applications of lime. Two methods of liming, hydrological source (catchment) liming and sand liming (in-stream liming), were used to reduce stream acidity. Electrofishing was carried out for several years before and after liming to monitor the recovery of salmon populations. Prior to liming, water chemistry differed between stream sub-catchments with differing land use. ANC, Ca concentrations and pH were lower, and Al concentrations were higher, in areas with conifers and acid grassland than in areas with improved grassland and broadleaf woodland. After liming pH increased, but the effects differed between sites and were dependent upon pH levels before any liming began, flow conditions, and the method of liming. An increase in pH during high flows was evident at many sites where acid episodes had occurred prior to liming. Diatom species richness and diversity were low, many sites supporting only 10–15 species. Correlations of richness and diversity with water chemistry were not significant but there was a tendency for low pH sites to support very few species. Species richness was highest in areas adjoining broadleaf woodland and improved grassland, and lowest in areas adjoining conifer plantations. Diatom species composition changed after liming and depended on the type of dominant land cover in the catchment areas and the method of liming. Species tolerant of low pH, in particular Eunotia exigua, became less abundant and were replaced by acid-sensitive species, predominantly Achnanthidium minutissimum . DAM index values and ecological quality ratios (EQR), which were both lower in conifer and acid grassland areas before liming than elsewhere, improved after liming and in many areas the ecological status class of limed streams became good or high. The change to diatom assemblages with predominantly acid-sensitive species after liming correlated with increasing numbers of juvenile salmon and their expansion upstream to sites that had lacked fish prior to liming.